Teacher Education for new times: Differentiate or die - Aspland, Tania (Journal of Research, Policy & Practice of Teachers and Teacher Education, 2018)
In order to address the crisis facing teacher education, the paper articulates a need to think differently about knowledge construction, curriculum design and implementation and the implications for teacher preparation. Further the focus on innovative pedagogies and learning engagement more closely aligned to new age learners, is argued as central to the reconstruction of teacher education programs away from a traditional focus on pre-determined content and regulated practices. This paper calls on the profession of teacher educators to differentiate on how we think about ourselves as knowledge workers for new times; to decide whether the current learning spaces of the academy are appropriate and whether our current role and positioning as academic lecturers is in need of reinvention. As a matter of urgency teacher educators must rethink the ways in which they design curriculum programs for teacher preparation before they are replaced by larger forces. In short teacher educators are called upon to differentiate or die.